2018
DOI: 10.1016/j.pcad.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Dual Antiplatelet Therapy Following Drug-Eluting Stent Implantation in Diabetic and Non-Diabetic Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Compared to L-DAPT, S-DAPT was associated with significant increase in rate of ST in non-DM patients. Duration of DAPT had no significant impact on rates of all-cause mortality, cardiac mortality, MI, ST and TVR among DM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…This might be because our analysis evaluated different trials and subgroups. Another meta-analysis published by Sharma et al [24] found that the risks for MI, TVR, and ST were similar in patients with DM after PCI treated by short-or long-term DAPT. From these results, it is not difficult to see that long-term DAPT is not superior to short-term DAPT in preventing ischemic events in patients with DM after PCI.…”
Section: Plos One Plos Onementioning
confidence: 96%
“…This might be because our analysis evaluated different trials and subgroups. Another meta-analysis published by Sharma et al [24] found that the risks for MI, TVR, and ST were similar in patients with DM after PCI treated by short-or long-term DAPT. From these results, it is not difficult to see that long-term DAPT is not superior to short-term DAPT in preventing ischemic events in patients with DM after PCI.…”
Section: Plos One Plos Onementioning
confidence: 96%
“…The patients with DM were low in these trials and therefore these results should not be applied to diabetic patients. In addition, although some clinical trials revealed that the clinical outcomes with short DAPT were non-inferior to those with long DAPT in DM patients, the duration of short DAPT was around 6 months [49,50]. In the present study, the CAS evaluations demonstrated that the rate of the minimum NIC of grade 0 was significantly higher in the DM group than in the non-DM group 3-5 months after DES implantation, which is consistent with the concept that DM is a factor that increases the thrombotic risk even in the early phase.…”
Section: Discussionmentioning
confidence: 99%
“…The described biofunctionalized stent might find particular application in clinical settings in which double antiplatelet therapy, particularly in the long term, is considered too risky for the patient as interruptions of antiplatelet therapy can lead to life-threatening stent thrombosis. 54 A more extensive preclinical study is planned to verify these promising initial observations. CONCLUSION 316L steel stents were functionalized by attachment of anti-VEGFR2 human scFv antibody fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Early coverage of stent surfaces with ECs would also reduce susceptibility to acute and subacute stent thrombosis compared to drug eluting stents. The described biofunctionalized stent might find particular application in clinical settings in which double antiplatelet therapy, particularly in the long term, is considered too risky for the patient as interruptions of antiplatelet therapy can lead to life‐threatening stent thrombosis . A more extensive preclinical study is planned to verify these promising initial observations.…”
Section: Discussionmentioning
confidence: 99%